CHARACTERIZATION AND 3D MODELLING OF NATURAL FRACTURE ON BASEMENT OUTCROP AT BATAM ISLAND, KEPULAUAN RIAU PROVINCE - FESTIAN PRAKOSO (22020304), YEHEZKIEL
Fractures are the most abundant structure in the earth's crust. Fractures are present in all types of rock, and can be observed at various scales of observation. Although their presence is very common, the distribution of fractures is very difficult to predict and characterize. The presence of fracture has a very significant effect on the physical and hydraulic properties of rock, so it becomes a concern in various geological applications. This study aims to determine the characteristic of natural fracture, distribution of natural fracture, fault damage zones (FDZ), and to build a 3D fracture model based on outcrop analog data. The study focused on natural fracture on granitic basement outcrop along the northeast coast of Batam Island, Kepulauan Riau Province, Indonesia (1?8'0” N – 1?12'30” N and 104?4'0” E – 104? 9'0” E). Measurement of natural fracture data using linear scanline and window scanline methods. The number of natural fracture data is 6,847 fractures, which is then classified into joint, shear, and vein. The joint strikes are north-northwest (NNW) and east (E), the shear strikes are northeast (NE) and east-southeast (ESE), and the vein strikes are north (N) and northeast (NE). Natural fractures have a relatively steep dip (600 – 750). Natural fractures in the study area are fractal following the power law distribution. The value of fracture intensity varies in the range of 6 – 56 fractures/m, while the value of fracture density varies in the range of 0.07 – 0.63 cm/cm2. The distribution of fracture intensity and density is controlled by fault and basement lithology. The values of fracture intensity, density, porosity, and permeability inside the fault damage zone are greater than those outside the fault damage zone. The 3D fracture model was built using the Discrete Fracture Network (DFN) method based on analog outcrop data. The fracture model shows a fracture distribution that is close to outcrop condition, and produces the values of fracture porosity in the range of 0.01 – 1.2% and fracture permeability in the range of 0.01 – 24.2 darcy.